Real‐world dosing characteristics and utilization of parenteral treprostinil in the outpatient setting. (12th January 2022) - Balasubramanian, Vijay P.; Safdar, Zeenat; Sketch, Margaret R.; Broderick, Meredith; Nelsen, Andrew C.; Lee, Dasom; Melendres‐Groves, Lana
Abstract: Real‐world dosing and titration of parenteral (subcutaneous, SC; intravenous, IV) prostacyclin, a mainstay of pulmonary arterial hypertension (PAH) treatment, is not always consistent with prescribing information or randomized trials and has yet to be adequately characterized. The current study describes real‐world outpatient dosing and titration patterns over time, in PAH patients initiated on SC or IV treprostinil. A longitudinal, cross‐sectional analysis of medication shipment records from US specialty pharmacy services between 2009 and 2018 was conducted to determine dosing and titration patterns of SC or IV treprostinil in the outpatient setting beginning with the patient's first shipment. The sample for analysis included shipment records for 2647 patients (IV = 1040, SC = 1607). Although more patients were started on SC treprostinil than IV, median initial outpatient IV treprostinil dose (11 ng/kg/min at month on therapy one [MOT1]) was consistently and statistically significantly higher than initial outpatient SC dose (7.5 ng/kg/min at MOT1; p  < 0.01). However, the SC treprostinil dose acceleration rate (DAR) was more aggressive from MOT1 to MOT6, MOT12, and MOT24, leading to a higher dose achieved at later timepoints. All between‐group DAR differences were statistically significant ( p  < 0.001). This study provides evidence that real‐world prescribing patterns of parenteral treprostinil in the outpatient setting differs from dosing described in pivotal trials, with important differences between SC and IV administration. Although initial outpatient IV treprostinil dosing was higher, SC titration was accelerated more aggressively and a higher dose was achieved by MOT3 suggesting that factors specific to SC administration (e.g., site pain) may not limit dosing and titration as previously thought.